(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Libraries have long been centers of knowledge, providing resources and spaces for learning. However, with the rise of digital technologies, interdisciplinary research, and the growing complexity of academic work, libraries have evolved far beyond their traditional role. Today, one of the key services that libraries offer is research support—a comprehensive suite of services designed to assist researchers throughout the various stages of the research process, from identifying resources to disseminating findings. In this article, we will explore what research support services in libraries are, why they are important, and how they contribute to the advancement of research in academic and professional settings.